Pulse Pattern-Modulated Strategy for Harmonic Current Components Reduction in Three-Phase AC-DC Converters - Davari, P.; Zare, Firuz; Blaabjerg, F. (2016)
© 2016 IEEE. Generated harmonic current as a consequence of employing power electronics converter is known as an important power quality issue in distribution networks. From industry point of view, complying with international standards is mandatory; however, cost and efficiency are two other important features, which need to be considered in order to be competitive in the market. Therefore, having a flexibility to meet various requirements imposed by the standard recommendations or costumer needs is at most desirable. This makes the generated harmonic current mitigation a challenging task especially with three-phase diode-bridge rectifier, which is still preferred in many power electronic systems. This paper addresses a novel current modulation strategy using a single-switch boost three-phase diode-bridge rectifier. The proposed method can selectively mitigate current harmonics, which makes it suitable for different applications. The obtained results at experimental and simulation levels verify and confirm the robustness of the proposed approach.